Persepsi Orangtua terhadap Pemanfaatan Barang Bekas sebagai Alat Permainan Edukatif Anak Usia Dini - Jazariyah Jazariyah; Ervina Latifah; Nur Zahra Atifah (Institut Agama Islam Negeri Madura, 2021)
Second hand goods are products has been unused or no longer required, but second hand goods still have useful if processed back properly.This research aims to review the extent to which perception parents have early childhood on the use second hand goods to be used as a gaming console. educativeThis study using descriptive approach by using a method of. Survey. Data collection is done using a questionnaire distributed to 25 parents who became a sample of his observations research is that most parents from early childhood of several cities in the west java have been enough to have understanding on the use thrift as educational gaming console child especially to lessons learned from the house.